2005
DOI: 10.1521/aeap.2005.17.6.555
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and HIV Risks Among Acculturating Asian Indian Men in New York City

Abstract: This community-based, qualitative study explored social capital resources and their influences upon HIV risk behaviors in a sample of 17 heterosexual Asian Indian immigrant men residing in New York City. Our study defined social capital as the resources available to individuals and society through social relationships. At the family, peer, and community levels, social capital's influence appeared to reduce acculturative stress and HIV risks. However, participants who lacked sexually transmitted infection and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 14 publications
2
39
0
Order By: Relevance
“…Although research on the HIV vulnerability of Indian immigrants in western countries (including Canada) remains limited, studies of this population have identified a number of risk factors within South Asian, including Indian, communities. These include a lack of accurate knowledge about sexually transmitted infections and HIV transmission, the stigma borne by individuals and families affected by HIV, denial of HIV-related risks, difficulties in negotiating and adopting safer sex practices within intimate relationships, and constrained access to HIV-related services (Bhattacharya 2004(Bhattacharya , 2005Gagnon et al 2010;Kteily-Hawa 2013;Majumdar 2013;Vlassoff and Ali 2011). In both India itself and in South Asian communities in the West, HIV infection is largely perceived as a result of non-normative, and thus immoral, sexual behaviours, such as sexual 'promiscuity' , sex with sex workers, and same-sex sexual encounters (Chin et al 2005;Ekstrand et al 2012;Vlassoff and Ali 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research on the HIV vulnerability of Indian immigrants in western countries (including Canada) remains limited, studies of this population have identified a number of risk factors within South Asian, including Indian, communities. These include a lack of accurate knowledge about sexually transmitted infections and HIV transmission, the stigma borne by individuals and families affected by HIV, denial of HIV-related risks, difficulties in negotiating and adopting safer sex practices within intimate relationships, and constrained access to HIV-related services (Bhattacharya 2004(Bhattacharya , 2005Gagnon et al 2010;Kteily-Hawa 2013;Majumdar 2013;Vlassoff and Ali 2011). In both India itself and in South Asian communities in the West, HIV infection is largely perceived as a result of non-normative, and thus immoral, sexual behaviours, such as sexual 'promiscuity' , sex with sex workers, and same-sex sexual encounters (Chin et al 2005;Ekstrand et al 2012;Vlassoff and Ali 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Processes of immigration and settlement further complicate the HIV vulnerability of Indian immigrants, because they often have to deal with the accompanying problems of loss of social support (eg with their extended family in India), financial instability or outright poverty, loneliness, social isolation, and racism (Bhattacharya 2005;Kteily-Hawa 2013;Vlassoff and Ali 2011). In her study of Indian immigrant men in New York City, for instance, Bhattacharya (2005) found that acculturative stress -such as loneliness, frustration, mental health problems, and job stress -rendered men vulnerable to HIV infection by driving them to resort to casual sexual partners or sex workers, as well as substance abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling for population-level variables, higher social capital has been shown to be associated positively with self-rated health and negatively with mortality (Cohen et al, 1997;Kawachi, 1999;Kawachi, Kennedy, Lochner, & Prothrow-Stith, 1997;Kawachi, Kennedy, & Glass, 1999;Philadelphia Health Management Corporation, 2004;Subramanian, Kawachi, & Kennedy, 2001). Higher social capital is also associated with better social outcomes, including lower violence and better child welfare (Coleman, 1988;Furstenburg & Hughes, 1995;Kawachi, Kennedy, & Wilkinson, 1999;Parcel & Menaghan, 1993;Sampson, Raudenbush, & Earls, 1997), and with lower levels of risky behaviors associated with binge drinking (Weitzman & Kawachi, 2000), with infection with HIV and other STDs (Bhattacharya, 2005;Campbell, Williams, & Gilgen, 2002;Crosby et al, 2002;Crosby, Holtgrave, DiClemente, Wingood, & Gayle, 2003;Kawachi, Kennedy, & Wilkinson, 1999), and with drug use (Latkin, Williams, Wang, & Curry, 2005;Lindstrom, 2004;Lundborg, 2005). Recent data have shown that social capital is associated with people's self-rated health over and above the beneficial effects of personal social networks and support (Poortinga, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The three populations include: 1) new Hispanic immigrants from the Dominican Republic, Mexico and Central America [5][6][7] ; 2) West Indian (Caribbean) immigrants from Jamaica, Trinidad/Tobago and other anglophone Caribbean nations (data under analysis), and 3) South Asian immigrants from India (Indian Americans). 8 These data sets are employed to describe and compare sociodemographic characteristics of the three immigrant groups as well as some of the cultural and environmental factors that provide the context for risk and prevention of HIV/AIDS and other health challenges. We identify a number of risk and protective factors embedded to varying degrees in immigrants_ multiple cultures and sub-cultures.…”
Section: Introductionmentioning
confidence: 99%